Caracterización físico química y mineralógica del material de mena de la mina Montañita 1, Concesión minera Bella Rica Código 15, parroquia el Carmen de Pujilí, cantón Camilo Ponce Enríquez, provincia Azuay - Vidal Rivera, Jefferson Alfredo (2025)
The study area is located within the Bella Rica mining concession (Code 15), geographically situated in the parish of El Carmen de Pujilí, Camilo Ponce Enríquez canton, Azuay province. Geologically, it is found in the Pallatanga Unit, composed of basaltic andesites, tuffs, and breccias that have been intruded by Eocene porphyritic rocks. These rocks feature vein-like mineralization with quartz veins and veinlets. The present investigation aims to select the optimal sampling method based on mineralization; characterize the physical composition through tests of moisture content, specific gravity, apparent weight, porosity, and pH; conduct chemical analyses using fire assays to determine average assays and atomic absorption spectrophotometry to identify other minerals present in the ore. Additionally, mineralogical analysis was performed using X-ray diffraction techniques to quantitatively identify minerals, X-ray fluorescence to determine mineralogy, and petrographic testing with the construction of thin sections and polished sections. Finally, the most suitable metallurgical method for mineral recovery was proposed. Based on the data obtained, the most appropriate metallurgical method for the beneficiation process of the mineral of interest, gold, was proposed. This method also allows for the identification of penalty minerals that could present difficulties in extraction. The entire deposit of the site exhibits characteristics that favor the liberation of gold through cyanidation methods.